Implementation of Islamic Inheritance Law in Bulukumba, South Sulawesi: Community Knowledge and Attitudes and the Opinions of Scholars and Intellectuals - Mustari, Abdillah; Widjaja, Abdi; Herawati, Andi; Ma’ruf, Amar; Ilmi , Ani Auli (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study aims to analyze the relationship between the level of knowledge and attitudes of the community towards Islamic inheritance law in Lembanna Village, Bontobahari District, Bulukumba Regency. This study uses a combined quantitative and qualitative research method. Qualitative research uses a quantitative correlational approach, this study involved 95 randomly selected respondents aged 30 to 55 years. Data were collected through knowledge tests and Likert scale attitude questionnaires. Data were analyzed using Pearson Product-Moment correlation with the help of SPSS. While the quantitative method was carried out by in-depth interviews with academics, scholars, intellectuals, religious leaders and women leaders, then analyzed with the theory of maqāṣid al-sharī'ah. The results showed that the majority of respondents had a moderate level of knowledge and showed a neutral attitude towards Islamic inheritance law. The correlation test revealed a statistically significant positive relationship between knowledge and attitudes (r = 0.363; p < 0.05). This indicates that the higher a person's level of knowledge about Islamic inheritance law, the more positive their attitude towards its implementation. This study emphasizes that Islamic inheritance law must be reinterpreted from the perspective of the maqāṣid al-sharī'ah so that the law is not merely normative but rather provides gender and distributive justice, taking into account social changes in accordance with the views of Islamic scholars and intellectuals. This study contributes to the development of Islamic law and social psychology studies and emphasizes the importance of increasing knowledge as a foundation for promoting the acceptance and practice of Islamic law in a pluralistic social context.